The Effects of 8-week Online Yoga Training on Body Composition, Muscle Activity, Flexibility, and Balance - Inhye Cho; Kyung-tae Eo; Dongmin Kwak (Korea Institute of Sport Science, 2022)
PURPOSE The purpose of this study was to investigate the effects of an 8-week online yoga training on body composition, muscle activity, flexibility, and balance in males (n=7) and females (n=15). METHODS Twenty-two participants were recruited and divided into two groups (Exercise group, n=11 and control group, n=11). All participants had two visits. During the visits, body composition, muscle activity for forward and back-bending poses, flexibility for sitting-forward and back-bending poses, and balance for one-leg standing were determined. After 8-week yoga training, all measurements were re-performed. An independent t-test was performed to determine the difference between the exercise and control groups. A two-way repeated measures of ANOVA was used to assess the interaction effects (group*time). All values were represented as mean ± standard deviation. An α level was set at 0.05 for all analyses. RESULTS First, the height significantly increased (F=16.573, p=0.001) and body fat mass (F=7.109, p=0.015) and body fat percent (F=7.667, p=0.012) were significantly decreased after the 8-week online yoga training. Second, the muscle activity for vatus lateralis doing a back-bending pose (F=6.140, p=0.022) significantly increased after the 8-week online yoga training. Third, the flexibility on sitting-forward bending pose (F=4.661, p=0.043) and back-bending pose (F=11.650, p=0.003) were statistically increased after the 8-week online yoga training. Lastly, balance on the Center Of Pressure (COP) X (F=5.769, p=0.026) and the Center Of Pressure (COP) Y (F=4.365, p=0.05) significantly increased after the 8-week online yoga training. CONCLUSIONS This study will provide scientific evidence on improving exercise programs using online yoga training on physical activity.